Strength degradation characteristics and damage constitutive model of sandstone under freeze–thaw cycles - Zhongwen Wang; Meilu Yu; Lei Wang; Haotian Xie; Ying Xu; Luyu Wang (Scientific Reports, 2024)
Abstract Thorough investigation into the laws governing frozen rock damage in high-altitude and cold regions can offer valuable insights for advancing infrastructure construction, ecological environment protection, and sustainable development on the Qinghai-Xizang Plateau. This study combined with the seasonal variation patterns of frozen rocks in the Qinghai-Xizang Plateau, and processed the rock samples using a freeze–thaw interval of -20 °C~20 °C. Uniaxial compression test was conducted based on the MTS816 rock mechanics testing system. The porosity changes of rock samples with different freeze–thaw cycles were analyzed using the MesoMR12-060 H-I nuclear magnetic response analysis system. A rock freeze–thaw load coupled damage constitutive model was derived using the Lemaitre equivalent strain theory. Research has shown that during the freezing process, the pore water inside the rock sample is affected by the phase change of water-ice, resulting in frost heave force, which further promotes the expansion of the pore walls and the initiation of new cracks. When melted, pore water migrates towards newly formed micropores, thereby affecting the changes in the pores of rock samples. The increase in porosity at the micro level weakens the mechanical parameters of rocks at the macro level. The segmented freeze–thaw damage constitutive model based on Lemaitre equivalent strain theory can well fit the experimental results involved in this study, as well as the experimental results obtained by other researchers. The compaction stage can partially reflect the changes in sandstone pore structure under freeze–thaw cycles.